Please help me. I'm checking my answers. Evaluate the expression: Given 4x – 12, evaluate when x = -7

4x – 12, when x = -7 is the same thing as 4(-7) - 12, which equals -40. Your answer is -40.

s

Expert answered|vchutkan|Points 4850|

Question

Asked 3/22/2012 9:19:11 PM

Updated 2/21/2014 11:49:10 AM

0 Answers/Comments

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [2/21/2014 11:49:10 AM]

Rating

There are no new answers.

Please help me with checking my answers. Simplify by using the Distributive Property: 4a + 5(b – 2) **Weegy:**
4a + 5(b – 2)
= 4a + 5b - 10
**User:** Please help me with checking my answers. Simplify by using the Distributive Property: 8(3a + 2b – 5c) **Weegy:** Solution :
8(3a + 2b – 5c) = 24a + 16b - 40c **User:** Please help me check my answers. Simplify by Combining Like Terms: 14xy^3 – 22xy^3 + 5xy^3 **Weegy:** Solution :
14xy^3 – 22xy^3 + 5xy^3 by combining like terms
14xy^3 – 22xy^3 + 5xy^3 = -3xy^3 **User:** Applying PEMDAS, simplify these expressions: 6 + 4(3^2) – 20 **Weegy:** Solution :
Applying the PEMDAS
6 + 4(3^2) – 20
6 + 4(3^2) – 20 = 6 + 4 (9) - 20 ;
= 6 + 36 - 20
= 42 - 20
= 22 **User:** Applying PEMDAS, simplify: -12 – 48 ÷ 6 x 3^2 + 10 **Weegy:** Solution :
-12 – 48 ÷ 6 x 3^2 + 10
= -12 – 48 ÷ 6 x 9 + 10
= -12 – 8 x 3^2 + 10
= -12 – 8 x 9 + 10
= -12 – 72 + 10
= -12 – 62
= -74
**User:** Simplify the espressions with grouping symbols: 14 – [ 3 + (8 – 2)] **Weegy:** Solution :
14 – [ 3 + (8 – 2)]
= 14 – [ 3 + 8 – 2]
= 14 – 3 - 8 + 2
= 5 **User:** Evaluate the expression: Given 4x – 12, evaluate when x = -7 **User:** Given 3x^2 + 2x – y, evaluate when x = -3 and y = 9 (More)

Question

Expert Answered

Updated 7/16/2014 11:40:23 AM

2 Answers/Comments

4x – 12, x = -7

= 4(-7) - 12

= -28 - 12

= -40

= 4(-7) - 12

= -28 - 12

= -40

Added 7/16/2014 11:39:09 AM

This answer has been confirmed as correct and helpful.

3x^2 + 2x – y, x = -3 and y = 9

3(-3)^2 + 2(-3) - 9

= 3(9) - 6 - 9

= 27 - 6 - 9

= 12

3(-3)^2 + 2(-3) - 9

= 3(9) - 6 - 9

= 27 - 6 - 9

= 12

Added 7/16/2014 11:40:22 AM

This answer has been confirmed as correct and helpful.

33,646,282

questions answered

There are no comments.